High-Frequency EEG Oscillations: New Biomarker in Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at University Medical Center Utrecht, The Netherlands and other centers review the pathophysiology, clinical relevance, identification, and interpretation of high-frequency oscillations (HFOs, >80Hz) in the epileptic EEG.